Defining "Satanic Literature" : a complex genre. - Phneah, Ellyne Yi Lin. (2011)
This paper aims to define the term “Satanic Literature” by examining the ways certain literary texts challenge the politics of Christianity during the period they were written. Though the term has been used to describe certain texts over the years, it has not been properly characterized. What makes a piece of literature offensive to Christianity? What lines does it cross? Defining this is a complicated process. Christianity’s politics evolved over time, and so did the meaning of Satanism, which points to its inconsistent definition. The bible is not a straightforward source and there have been arguments pertaining to what exactly it is, and whether it is an accurate word of God. To further illustrate this concept, I will be analyzing three important texts from a range of time periods: Marlowe’s “Doctor Faustus”, Milton’s “Paradise Lost” and Brown’s “The Da Vinci Code”. These texts are chosen because of their heavy theological contents and the controversies they have stirred in Christianity. Because they are literary works from three different genres of three separate time periods in Christianity, textual analysis will not only show how they fit into the satanic literature genre but how this genre has evolved over the years.